1999
DOI: 10.1038/sj.ijo.0801036
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin concentration in moderate and severe obesity: relationship with clinical, anthropometric and metabolic factors

Abstract: OBJECTIVE: To study clinical, anthropometric and metabolic determinants of serum leptin concentrations in a series of patients with a wide range of obesity. SUBJECTS: 400 patients, 116 males and 284 females, aged 44 AE 12.3 years with body mass index (BMI) ranging from 31 to 82 kgam 2 (mean 41.4 AE 7.1). MEASUREMENTS: Energy intake by 7-day recall, resting energy expenditure (REE) by indirect calorimetry, body composition determined by bioelectrical impedance; C index, an anthropometric index of abdominal fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
77
1
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 22 publications
15
77
1
6
Order By: Relevance
“…In the present study, we found a positive exponential association between fasting plasma leptin and FM, which is in agreement with previous findings (6,18,28). Waist-to-hip ratio, the ratio between preperitoneal and subcutaneous abdominal fat, and truncal fat percentage were not independently related to fasting plasma leptin concentration.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we found a positive exponential association between fasting plasma leptin and FM, which is in agreement with previous findings (6,18,28). Waist-to-hip ratio, the ratio between preperitoneal and subcutaneous abdominal fat, and truncal fat percentage were not independently related to fasting plasma leptin concentration.…”
Section: Discussionsupporting
confidence: 93%
“…However, our findings are in agreement with previous findings from studies on 150 to 200 subjects (37,38). In contrast, a relationship between leptin and body fat distribution has been described in a number of studies (28,39,40). These conflicting findings might be due to differences in methods used to assess fat distribution as well as to differences in subject characteristics and intersubject variation in body composition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In regard to serum leptin levels, the statistically significant interaction between the duration of feeding and high-fat diet suggests that both factors are involved in leptin regulation. This finding is in good accordance with reports that correlate adiposity with hyperleptinemia (26,27), since leptin, as an adiposity FIG. 2.…”
Section: Discussionsupporting
confidence: 93%
“…Há uma ampla distribuição dos níveis de leptina sérica para cada valor de IMC, sendo que alguns obesos poderiam ser considerados leptino-deficientes (17,28,29). O estudo dos parentes heterozigotos dos indivíduos com deficiência congênita de leptina evidenciou que estes indivíduos tinham níveis mais baixos de leptina e apresentavam maior percentual de gordura que indivíduos controle (30).…”
Section: Leptinaunclassified